HALAL CERTIFICATION PROCESS: PROBLEMS AND SOME SOLUTIONS (Conferencea, 2023)
In modern times, every state cares about its economic situation. The development of the market and providing it with high-quality goods is one of the goals of the development of the economy, social and political spheres. Various processes are used to confirm the quality of the goods, one of these is the "Halal" certification process. Despite the fact that this process has become widespread relatively recently, the process itself and the product that has passed the certification process are in great demand. The process of "Halal" certification, however, also includes problematic issues. The article examines the aspects of the "Halal" certification process, as well as various aspects of the "Halal" certification process in order to identify problems and develop recommendations for their solution. To achieve this goal, the author analyzes the practice of the Federation of Malaysia, the United Arab Emirates, etc.